Exclusión de la pensión alimenticia a los obligados subsidiarios por adolecer de enfermedades catastróficas - Guapi Naula, Angel Rogelio (2019)
Within the research proposed, it has been possible to establish the need to regulate the legal situation of people suffering from catastrophic illnesses at the moment in which pensions are established, which are regulated in the Organic Code of Children and Adolescence of Ecuador and is a right for children and adolescents, but in none of the articles referred to in Article 35 of the Constitution of Ecuador. It is for this reason that there is evidence of the antinomy and violation to which the parents who unfortunately go through these catastrophic pathological conditions are exposed, which in one way or another reaffirms the lack of probity and the existing normative breach for these people, of equal It must be stated that it does not take into account what is also established in Article 3 of the Organic Law on Guarantees and Constitutional Control, as it relates to the weighting of rights……….